Layanan Bimbingan Kelompok Belajar Dalam Meningkatkan Interaksi Sosial Siswa Kelas IX Cerdas Istimewa Di SMP Negeri 5 Kota Tasikmalaya - Taqwa, Dita Imtisal; Saputra, Wahyu Nanda Eka; Handayani, Dra Nur (Jurnal Eksplorasi Bimbingan dan Konseling, 2024)
Social Interaction is a way of building reciprocal relationships that influence each other between individuals, individuals and groups, or groups and groups in these reciprocal relationships can form behavior. Efforts are needed to improve social interaction by providing study group guidance services. The purpose of this study is to determine the effectiveness of study group guidance services in improving social interaction of class IX Smart Special students at SMP Negeri 5 Tasikmalaya. The type of research used is experimental research using a one group pretest-posttest design. The subjects of this study were 19 students. Based on the calculation of the pre-test score, 9 students were selected as research subjects with levels of social interaction in the medium and low categories. Validity test analysis with the product moment formula and reliability test analysis with the alpha cronbach formula. Data collection using social interaction questionnaire instruments and observation sheets. Data analysis techniques using the Wilcoxon signed ranks test analysis. The results of the study showed that the Z value obtained was -2.668 with a p value of Asymp. Sig (2-Tailed) of 0.008 where the value is less than the critical limit of the study, which is 0.05. The average score of students' social interaction before the study group guidance was carried out was 100.66 which is in the low category, after the study group guidance was carried out it increased by an average of 39.1 points to 139.78 which is in the high category. Based on the explanation above, it can be concluded that the study group guidance service is effective in improving the interaction of class IX Smart Special students at SMP Negeri 5 Tasikmalaya.